Reduced levels of NR2A and NR2B subunits of NMDA receptor and PSD-95 in the prefrontal cortex in major depression - Feyissa, Anteneh M.; Chandran, Agata; Stockmeier, Craig A.; Karolewicz, Beata (Progress in neuro-psychopharmacology & biological psychiatry, 2009)
Recent neuroimaging and postmortem studies have demonstrated abnormalities in glutamatergic transmission in major depression. Glutamate NMDA (N-methyl- d-aspartate) receptors are one of the major mediators of excitatory neurotransmission in the central nervous system. At synaptic sites, NMDA receptors are linked with postsynaptic density protein-95 (PSD-95) that plays a key role in mediating trafficking, clustering, and downstream signaling events, following receptor activation. In this study, we examined the expression of NMDA receptor subunits NR1, NR2A, and NR2B as well as PSD-95 in the anterior prefrontal cortex (PFC) using Western blot method. Cortical samples were obtained from age, gender and postmortem interval matched depressed and psychiatrically healthy controls. The results revealed that there was a reduced expression of the NMDA receptor subunits NR2A (− 54%) and NR2B (− 48%), and PSD-95 protein level (− 40%) in the PFC of depressed subjects relative to controls, with no change in the NR1 subunit. The alterations in NMDA receptor subunits, especially the NR2A and NR2B, as well as PSD-95 suggest an abnormality in the NMDA receptor signaling in the PFC in major depression. Our findings in conjunction with recent clinical, cellular, and neuroimaging studies further implicate the involvement of glutamate neurotransmission in the pathophysiology of depression. This study provides additional evidence that NMDA receptor complex is a target for discovery of novel antidepressants.